King's sister--queen of dissent : Marguerite of Navarre (1492-1549) and her evangelical network - Reid, Jonathan A. (Leiden ; Boston : Brill, 2009)
"This study reconstructs for the first time Marguerite of Navarre's leadership of a broad circle of nobles, prelates, humanist authors, and commoners, who sought to advance the reform of the French church along evangelical (Protestant) lines. Hitherto misunderstood in scholarship, they are revealed to have pursued, despite persecution, a consistent reform program from the Meaux experiment to the end of Francis I's reign through a variety of means: fostering local church reform, publishing a large corpus of religious literature, high-profile public preaching, and attempting to shape the direction of royal policy. Their distinctive doctrines, relations with major reformers - including their erstwhile colleague Calvin - involvement in major Reformation events, and the impact of their unsuccessful attempt are all explored."--Publisher's website
Cover -- Title Page -- Copyright Page -- Dedication -- Table of Contents -- List of Tables -- Acknowledgements -- Abbreviations and Short Titles -- Introduction. Resolving a Riddle: Marguerite of Navarre and the Early French Reformation -- A Twofold Riddle -- French Reformation Historiography: The "Magnificent13; Anarchy" -- Structure of Study -- Chapter One -- The Early Reformation in France -- Evangelical Growth -- The Crisis of Evangelicalism -- The Reformed Ascendancy -- Chapter Two -- Mapping the Navarrian Network -- Contemporary Signposts -- Sources for Reconstructing the Navarrian Network -- Dramatis Personae -- Chapter Three -- The Valois Trinity Takes Power: New Regime and Church Reform, 15158211;1521 -- The Royal Trinity -- Marguerite: The Trinity's Minor Partner and Her New Powers -- Marguerite's Support of Francis's Rule: Foreign Affairs and the Concordat -- The Royal Family's Religion and Late Medieval Reform -- Leading Characteristics of Marguerite's Religion -- Chapter Four -- The Fabrist Background to the Navarrian Network -- "Ante illustrationem Evangelii:" Evangelical Self-awareness -- The Fabrists' Career -- From "Barbarian Captivity" to the "Babylonian Captivity:" The Restoration of Learning -- Before Meaux: A Season of Growth and Strife -- Prepared but not Destined for Meaux -- Chapter Five -- The Meaux Experiment I: From Clerical Reform to Evangelical Renewal, 15188211;1523 -- Clerical Reform to 1521 -- Evangelical Renewal, 15218211;1523 -- Chapter Six -- The Meaux Experiment II: Model for National Reform, 15218211;1523 -- Bri231;onnet's 'Band' and 'Captain' Marguerite -- A Reform Program Rebuff ed, Fall 1522 -- The Cold War Heats Up, May8211;December 1523 -- The Bourges Breakout, November 15238211;February 1524 -- Chapter Seven -- From Meaux to Madrid: The Network Knits Together, 15248211;1526 -- Birth of the Network: An International "Fraternal Alliance" -- The French Evangelical Reform Program and the German Connection -- The Invention of the French Evangelical Press in 1525 -- Leadership and Strategy8212;Doctrine and Purpose -- Chapter Eight -- Resurrecting King and Reform, 15258211;1530 -- The King in Captivity and Reform in Exile, 15258211;1526 -- Reform Held Hostage, 15268211;1530 -- Chapter Nine -- Legitimating the Evangelical Movement, 15318211;1539 -- Prologues to the Paris Campaign, 15318211;1534 -- Evangelical Buildup and Breakdown in Paris, 15338211;1535 -- An Improbable Religious Concord, 15338211;1536 -- Volume -- 2 -- Chapter Ten -- The 'Sons of Apollo' in the Service of Christ -- Poets as Religious Leaders -- Polemics and Piety -- Chapter Eleven -- Secret Diplomacy and Religious Dissimulation, 15408211;1549 -- "The Emperor is Hypocrisy and the Pope the Devil": Evangelical Diplomacy at the Court of Francis I, 15408211;1547 -- Building Evangelical Institutions: Claude Baduel and G233;rard Roussel -- The Dynamics of Separation: The Navarrian Network and Calvin -- Conclusion -- Towards the Wars of Religion -- Appendix A -- Additions and Corrections to the Correspondence of Marguerite of Navarre -- Additions and Corrections -- Index: Changes to Letter Numbers -- Appendix B -- Books Related to the Navarrian Network -- I.A Checklist of Books Related to the Navarrian Network -- II. Manuscript Books of the Navarrian Network -- III. The Navarrian Network's Reading List 1524.
Includes bibliographical references (pages 723-769) and index.
Print version record.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
eBooks on EBSCOhost
Keywords: Marguerite, -- Queen, consort of Henry II, King of Navarre, -- 1492-1549.; Marguerite, -- Queen, consort of Henry II, King of Navarre, -- 1492-1549; Marguerite, -- Queen, consort of Henry II, King of Navarre, -- 1492-1549.; Reformation -- France; Evangelicalism -- France -- History; Queens -- Navarre (Kingdom) -- Biography; Réforme (Christianisme) -- France; Évangélisme -- France -- Histoire; Reines -- Navarre (Royaume) -- Biographies; BIOGRAPHY & AUTOBIOGRAPHY -- Historical; HISTORY; Evangelicalism; Queens; Reformation; Navarre (Kingdom); France; Reformation -- France -- History; Evangelicalism -- France -- History; Queens -- Navarre (Kingdom) -- Biography; Reformationen -- Frakrike; Evangelikal teologi -- historia -- Frankrike; Biographies; History; Biographies; Biographies